A Critical Discourse Analysis on the Representation of Female Idols in the “Idol” Song Lyric by Yoasobi: From the Feminism Point of View - Farisya, Ghaida; Dewanty, Via Luviana (Universitas Pendidikan Indonesia (Indonesia University of Education), 2023)
Each song lyric has a message that the writer wants to convey to the listener about what the writer feels and thinks. This research discusses how Japanese female idols are represented in the opening soundtrack of the anime song “Oshi no Ko” which is currently being discussed among Japanese idol fans. The song titled “Idol” is the work of a duo band known as Yoasobi, telling a story of anxiety and sadness in the romance of Japanese youth life but accompanied by uplifting techno music. When song lyrics are made based on commercial interests, the meaning of the text should be criticized to find out who is in a dominating position and who is not. The song “Idol” in this research is analyzed using Sara Mills’sCritical Discourse Analysis (CDA) (1997) with a feminist perspective to analyze the presentation of the storyteller (subject) and the told (object). The results of this study show that the position of female idols as objects is shown as a figure who does not talk about herself much, her desires and feelings are less well conveyed. Female idols are shown more from the fans’ point of view as the position of the storyteller (subject). The position of female idols in the lyrics is only shown by stereotypical idol characters who are required to have a positive image, have high loyalty to fans, are required to be perfect by covering all flaws, and are prohibited from dating. Although the song “Idol” is an anime soundtrack that discusses the other side of idol life, in this song, the opportunity to voice the thoughts and what female idols want to express is not well displayed. Thus, the lyricist only presents female idols based on what they want for the sake of desire and sexual objects. This research only uses one main data source, namely song lyrics. It is hoped that future research can use a variety of main data sources such as anime or manga.